(untitled) - FAO (Rome, 1996)
This publication is directed toward people in charge of EIA(Environmental Impact Assessment) and EA (Environmental Auditing) in the pulp and paper industry. It is intended as an overview of the diffrent factors that must be addressed in an EIA and as general guidance for people planning, designing or assessing pulp and paper projects or operating sites. It provides background information about both the paper industry and the methods used for undertaking an EIA and an EA.
Keywords: forests and forestry,pulp